Effects of Chlorine Dioxide on the Postharvest Storage Quality of Fresh-Cut Button Mushrooms (Agaricus bisporus) - Weiwei Jin; Fengxian Su; Huan Zhou; Qiaojun Jiang; Yan Li; Haijun Zhao; Tao Luo (Horticulturae)
The application of chlorine dioxide (ClO2) in microbial safety and quality maintenance of fresh produce has received extensive attention. Fresh-cut button mushrooms (Agaricus bisporus) are prone to spoilage, resulting in a short shelf-life. In this study, ClO2 treatment was used to preserve fresh-cut button mushrooms, and its effect on maintaining the postharvest quality was investigated using sensory evaluation, weight loss, color, firmness, respiration rate, electronic-nose (E-nose) analysis and microbial analysis. During the 8 d storage, both the 50 and 100 mg·L−1 ClO2 treatment reduced the aerobic bacteria count on the surface of fresh-cut button mushrooms. However, the results showed that the 50 mg·L−1 ClO2 treatment but not the 100 mg·L−1 ClO2 treatment significantly inhibited the deterioration of comprehensive quality. The 50 mg·L−1 ClO2 treatment maintained the high sensory evaluation and pleasant volatile odor of fresh-cut button mushrooms as well as reduced the decreasing of fresh weight and firmness. Contrary to expectations, the application of ClO2 treatment showed worse appearances in color (lower L*, higher a*, b* and browning index) of fresh-cut button mushrooms. Significant differences were observed between CK and ClO2-treated groups from day 0 to day 6, while there were no significant differences of a*, b* and browning index between CK and the 50 mg·L−1 ClO2 treatment at the end of storage (on day 8). In conclusion, the 50 mg·L−1 ClO2 can maintain the good quality of fresh-cut button mushrooms.